Critical Role of microRNA-21 in the Pathogenesis of Liver Diseases - Zhang, Ting; Yang, Zhihong; Kusumanchi, Praveen; Han, Sen; Liangpunsakul, Suthat (Frontiers in Medicine, 2020)
MicroRNAs are small non-coding RNAs that range in length from 18 to 24 nucleotides. As one of the most extensively studied microRNAs, microRNA-21 (miR-21) is highly expressed in many mammalian cell types. It regulates multiple biological functions such as proliferation, differentiation, migration, and apoptosis. In this review, we summarized the mechanism of miR-21 in the pathogenesis of various liver diseases. While it is clear that miR-21 plays an important role in different types of liver diseases, its use as a diagnostic marker for specific liver disease or its therapeutic implication are not ready for prime time due to significant variability and heterogeneity in the expression of miR-21 in different types of liver diseases depending on the studies. Additional studies to further define miR-21 functions and its mechanism in association with each type of chronic liver diseases are needed before we can translate the bedside observations into clinical settings.